2015
DOI: 10.1111/jdv.13217
|View full text |Cite
|
Sign up to set email alerts
|

Epidermotropic diffuse large B‐cell lymphoma infiltrating the umbilicus, presenting as Sister Mary Joseph's nodule

Abstract: EditorSister Mary Joseph's nodule is an umbilical metastatic nodule from an intra-abdominal tumour.1 The primary origin is usually the gastrointestinal or genital system, but on rare occasions, this pathology originates from lymphoma. [2][3][4] We describe herein a case of diffuse large B-cell lymphoma (DLBCL) infiltrating only in the umbilicus, histologically presenting as epidermotropism, as an atypical histological presentation of B-cell lymphoma.A 36-year-old Japanese man consulted with us about a 1-week h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although this case was initially interpreted as a DLBCL, the distinctive clinical presentation with a disseminated skin rash resembling pityriasis rosea was unusual for DLBCL. In addition, the orderly multinodular non-effacing growth pattern around nerves, blood vessels, and the eccrine coil without diffuse infiltration and the presence of epidermotropism, which has been only rarely reported in DLBCL, were not compatible with DLBCL [15,16]. Moreover, there were many admixed smaller neoplastic B cells.…”
Section: Dermatology Online Journal || Case Reportmentioning
confidence: 90%
“…Although this case was initially interpreted as a DLBCL, the distinctive clinical presentation with a disseminated skin rash resembling pityriasis rosea was unusual for DLBCL. In addition, the orderly multinodular non-effacing growth pattern around nerves, blood vessels, and the eccrine coil without diffuse infiltration and the presence of epidermotropism, which has been only rarely reported in DLBCL, were not compatible with DLBCL [15,16]. Moreover, there were many admixed smaller neoplastic B cells.…”
Section: Dermatology Online Journal || Case Reportmentioning
confidence: 90%
“…The mechanism of epidermotropism of B-cell lymphomas is unknown, but Kakinuma et al 16 suggested a distinct interaction between the neoplastic B cells and particular epidermal chemokines and growth factors, similar to the mechanisms of epidermal involvement in T-cell lymphomas. Furudate et al 17 described a case of DLBCL with epidermotropism involving the umbilicus and found that malignant lymphoid cells expressed matrix metalloproteinase-9 in relation to decreased E-cadherin expression in the surrounding epidermis. This suggest that these changes promote migration of neoplastic lymphocytes into the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…26,29 More uncommonly, cases of DLBCLs with involvement of the epidermis have been described. 30,31 Clinically, these cases presented as solitary plaques or nodules and were sometimes associated with epidermal ulceration. Furudate et al 30 demonstrated in their case of epidermotropic DLBCL involving the umbilicus that lymphoma cells expressed matrix metalloproteinase-9 in association with diminished E-cadherin expression in the surrounding epidermis and postulated that these changes facilitated migration of malignant lymphocytes into the epidermis.…”
Section: Figurementioning
confidence: 99%